Teacher training of Veterinary professors in Spain - Mª Teresa Encinas Cerezo; Juan Antonio Gilabert Santos; José María Ros Rodríguez (Universitat Politècnica de València, 2015)
For a long time, no specific qualification or certified training in teaching have been not demanded to professors to access higher education.  Thus,  the  professor  teaching training  tends  to  be,  in  the  majority  of cases,  a  self-directed  process  that  does not have regulated path to deal with the continuous    and    necessary    update    to face   technological,   methodological   and structural  changes  of  higher  education  in recent years. However, many teachers are looking for training and improving their teaching skills through a dispersed and broad offer of courses and activities. Since he  creation  of  the  EHEA,  the  interest  of our  universities  and  professional  groups in  further  professional  training  of  their teachers, as a guarantee for the upgrading and quality in university teaching, have been  increased.  Through their institutes and departments of Educational Sciences, universities assume responsibility to offer to their teachers a highly variable offer of training activities.  In  this  article  different aspects  of  teacher  training  in  the  field of   the   Health   Sciences   and   Veterinary Medicine,   in   particular,   are   analysed: the   educational   spheres,   the   offer   of regulated and non-regulated training activities  (congresses,  meetings,  readings, publications,...), capacity and possibility of teaching  innovation  and  the  institutional assessment  and  the  evaluation  systems that   currently   exist   in   universities   and quality evaluation agencies.